2014
DOI: 10.7324/japs.2014.40301
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antifungal and antioxidant activity of Pelargonium graveolens essential oil

Abstract: The present study describes the chemical composition, antifungal and antioxidant activity of Pelargonium graveolens essential oil. The essential oil profile was determined by GC and GC-MS. The main compounds were citronellol (24.54%), geraniol (15.33%), citronellyl formate (10.66%) and linalool (9.80%). Minimal inhibitory concentrations (MIC) and minimal fungicidal concentrations (MFC) were recorded using the microdilution and macrodilution methods. Commercial antimycotic bifonazol was used as a control. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The literature report (Table 2) that oxygenated monoterpenes constitute the main group in every obtained essential oil (e.g. citronellol, geraniol, linalool or citronellyl formate) [5,11,19]. Comparing the available data (Table 2), all the studies show that for P. graveolens essential oil, citronellol is present in the most significant amount, reaching 37.5 % of the total oil of the plant growing in Tajikistan in Sharopov et al [20] research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature report (Table 2) that oxygenated monoterpenes constitute the main group in every obtained essential oil (e.g. citronellol, geraniol, linalool or citronellyl formate) [5,11,19]. Comparing the available data (Table 2), all the studies show that for P. graveolens essential oil, citronellol is present in the most significant amount, reaching 37.5 % of the total oil of the plant growing in Tajikistan in Sharopov et al [20] research.…”
Section: Discussionmentioning
confidence: 99%
“…P. graveolens is an aromatic and hairy shrub, erect up to 1-1.3 m tall and 1 m spread with soft to the touch and carved leaves, and usually small, pink flowers. It's essential oil yield is high and varies from 0.1-0.9 % v/w [13,19]. The oil is obtained from leaves, flowers and stalks [21].…”
Section: Pelargonium Spp Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil components of P. graveolens in the present study showed the highest amount of components such as citronellol (43.35 ± 0.48%) followed by menthan-2-one < cis-ρ- > (12.67 ± 0.06%), citronellyl formate (20.99 ± 1.73%), eudesmol < 10-epi-γ- > (2.71 ± 0.27%), rose oxide B (2.54 ± 0.05%), citronellyl propanoate (2.26 ± 0.10%), and citronellyl butanoate (1.58 ± 0.10%) while geraniol content was relatively low (< 0.50% not shown in data). Earlier studies also reported citronellol, geraniol, citronellyl formate, linalool, geranyl formate, menthone, isomenthone, and cis-rose oxide as major essential oil constituents 55 . However, N. cataria recorded nepetalactone < 4aα,7α,7aβ- > as a major essential oil constituent (91.43 ± 0.30%) followed by citronellyl propanoate (2.25 ± 0.02%) in Western Himalayan growing conditions.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, substitutes to chemical control are much needed now. Allelo-chemical compounds like plant extracts and essential oils are proposed as good alternatives [113] because they are biodegradable and less toxic to the environment [114]. The herbicidal effect of tea tree oil from M. bracteata was assessed by applying it on Panicum virgatum, Digitaria longiflora, Stachytarpheta indica, and Aster subulatus.…”
Section: Applications Of Tto In Agriculturementioning
confidence: 99%